The evolution of the terminological framework related to ICT in national normative and strategic documents - Angela GLOBA; Ala GASNAS (Acta et Commentationes, Sciences of Education, 2025)
This paper presents an analytical overview of the evolving definitions within the field of information and communication technologies, with particular emphasis on their application in the educational domain. The authors underscore the progressive development and formalization of related concepts within the legislative framework of the Republic of Moldova.